Hybrid multicriteria technique for international markets selection based on the analytic hierarchy process (2022)
Purpose: To present a rigorous technique for merchandise companies that are internationalizing and pursuit the best options of export markets to direct their products. Originality/value: The literature suggests that companies, especially small and medium enterprises (SME), due to their lack of experience when participating in international business, tend to employ uncertainty processes that affect in decision making when exporting. For this reason, an innovative multivariable technique for international markets selection (IMS) is presented, in which factors such as trade barriers, economics, cost, logistics and culture are considered. Design/methodology/approach: Consulting different databases obtained from the internet, it was possible to analyze the factors indicated above, which, in turn, are integrated by different variables. Thus, this work used a multivariable methodology and/or technique that is complemented with the analytic hierarchy process (AHP) to assign the weights of each factor and their respective variables; all this, including a survey among experts and members of the foreign trade department of the company under study, in this case, dedicated to the production of confectionery. Findings: According to the statistical data processed with the multivariable technique and weighted with the AHP process, the results suggest that by their score the best export markets are Ireland, Netherlands and Denmark. In this sense, the empirical evidence indicates that the pointed countries are the most attractive markets for the factors considered, as well as for their general features. Keywords: international markets selection, SME, exportation, internationalization, multivariable method